A case series on uterine inversion: diagnostic and surgical considerations - Agrawal, Harsha M.; Chafale, Sayalee (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Uterine inversion defined as descent of fundus of uterus to or through the cervix, so uterus is turned inside out. It may be puerperal and non-puerperal/gynecological, the latter being extremely rare. This rarity, delayed presentation and atypical presentation contribute to the clinical challenges. We present a case series four cases of uterine inversion including three cases of gynecological inversion and one case of puerperal inversion, managed at a tertiary care hospital in India. Clinical presentation, diagnostic methods, surgical techniques, and outcomes were documented. Non-puerperal cases were associated with submucosal fibroids and presented with mass protrusion, bleeding, and urinary complaints. Diagnosis was confirmed using clinical examination and magnetic resonance imaging (MRI). Surgical management included Huntington’s and Haultain’s techniques followed by hysterectomy. The puerperal case presented with acute hemorrhage postpartum and was managed successfully with Johnson’s maneuver and uterine balloon tamponade. It could be concluded from series that non-puerperal uterine inversion requires individualized surgical management based on underlying pathology. Acute puerperal inversion demands rapid resuscitation and repositioning to reduce maternal morbidity. MRI plays a pivotal role in diagnosis and planning. This series delineates the challenges involved in the diagnosis and operative management of the condition.